Importance of Considering the Middle Capillary Plexus on OCT Angiography in Diabetic Retinopathy - Onishi, Alex C.; Nesper, Peter L.; Roberts, Philipp K.; Moharram, Ganna A.; Chai, Haitao; Liu, Lei; Jampol, Lee M.; Fawzi, Amani A. (Investigative ophthalmology & visual science, 2018)
To quantify microvasculature changes in the superficial (SCP), middle (MCP), and deep capillary plexuses (DCP) in diabetic retinopathy (DR). Retrospective cross-sectional study at a tertiary academic referral center, in which 26 controls (44 eyes), 27 diabetic subjects without retinopathy (44 eyes), 32 subjects with nonproliferative retinopathy (52 eyes), and 27 subjects with proliferative retinopathy (40 eyes) were imaged with optical coherence tomography angiography (OCTA). Outcome measures included parafoveal vessel density (VD), percentage area of nonperfusion (PAN), and adjusted flow index (AFI) at the different plexuses. MCP VD and MCP AFI decreased with worsening DR, while PAN increased, mirroring changes within the DCP. The fitted regression line for MCP and DCP AFI were significantly different than the SCP, while DCP PAN differed from SCP PAN with disease progression. Higher SCP AFI and PAN were different in eyes with diabetes without retinopathy compared with controls. Unexpectedly, sex was found to independently influence MCP VD and AFI with worsening disease. OCTA parameters in the MCP and DCP displayed parallel changes with DR progression, different from the SCP, emphasizing the importance of physiologic considerations in the retinal capillaries. Thus, segmentation protocols that include the MCP within the SCP may be confounded. A difference in DCP PAN with worsening DR was unmasked relative to a prior study that included the MCP with SCP. We confirm that SCP AFI and PAN may serve as early indicators of microvascular changes in DR and identify an interaction between sex and the MCP deserving further study.